Performance of a plate‐wave energy converter integrated in a floating breakwater - Siming Zheng; Mike Meylan; Xiantao Zhang; Gregorio Iglesias; Deborah Greaves (IET Renewable Power Generation, 2021)
Abstract A plate‐wave energy converter (pWEC) moored in front of a floating stationary breakwater is considered. The pWEC is composed of a submerged flexible plate with piezoelectric layers bonded to both faces of it. Hence the elastic motion of the plate excited by water waves can be transformed into useful electricity due to the piezoelectric effect. To evaluate the performance of the breakwater‐attached pWEC in terms of wave power absorption and wave attenuation, a hydroelastic model based on linear potential flow theory and the eigenfunction matching method is developed with the electromechanical and the hydrodynamic problems of the pWEC coupled together. The pWEC can be either simply supported or clamped at the edge. A multi‐parameter analysis is carried out with the employment of the present model. Effects of the width, submergence and edge types of the plate, together with the scales of the breakwater, including its width and draft, on wave power absorption and wave attenuation, are examined. As the pWEC moves towards a deeper position, the main peaks of the frequency response of the wave power absorption efficiency become lower and narrower. In contrast, its effect on wave attenuation is limited.